Rethinking Muscle Testing: Dynamic EMG Studies of Elbow Positioning as a Differentiator of Pronator Teres and Quadratus Functions - Lunasin, Ray M; Capell, William; Kaufman, Kenton R; Shin, Alexander Y (The Journal of hand surgery (American ed.), 2025)
This study analyzed the contributions of pronator teres (PT) and pronator quadratus (PQ) during different forearm pronation tasks using dynamic EMG to assess whether the function of these two muscles can be distinguished by elbow positioning during muscle activation testing. Twelve healthy subjects were studied. Each subject underwent intramuscular dynamic EMG of the PT and PQ to evaluate muscle activation during forearm pronation at varying elbow flexion angles (elbow fully extended, elbow flexed 90°, and elbow maximally flexed). EMG data were collected under three conditions: maximal voluntary isometric contraction, no resistance, and high resistance. The primary outcome was the proportion of participants who exceeded the muscle activation threshold at each testing position. All participants demonstrated muscular activation of the PQ and PT, with all motions assessed when resistance was applied. However, the muscular activity varied when participants completed movements without resistance. Seven participants (58.3%, [32%-81%]) demonstrated simultaneous activation (≥10% maximal voluntary isometric contraction) of the PQ and PT with the elbow fully extended and elbow flexed 90°, whereas nine (75%, [43%-95%]) demonstrated simultaneous activation with the elbow maximally flexed. Six of twelve participants (50%, [21%-79%]) demonstrated simultaneous activation during all movements assessed with and without resistance. The findings suggest that the function of the PT and PQ cannot be isolated by elbow flexion positioning. When a precise functional assessment of the pronator group is needed for preoperative planning, a dynamic EMG assessment should be performed.